The study of customer complaints on Kancil services / Faizal Hamid - Hamid, Faizal (2000)
To reduce the number of complaints and increase number of satisfaction, they company must develop methods to effectively handle individual complaints as they occur and make strategic changes in business practices to reduce complaints over time. Statistical Programme Software System (SPSS) version 9 was used in order to get the accurate data from Faculty of Quantitative Science and Information Technology, laboratory 7 and 8, MARA University of Technology, Shah Alam, Selangor. Excellent services provided to the Kancil owners are needed in realizing full potential for the company. The ability of an organization to earn positive word-of-mouth or goodwill by its customers is on the services provided. Therefore, long waiting time or delivery of the car, Sales Personnel behaviors at Branches and Dealers in communicating and interaction between the service providers and customers should be avoided. Qualities of Kancil also are the key factors to the company to ensure the performance, engine and safety features of the car. These are essential in order to earn high reputation that reflects the organization's credibility, thus attracting customers and prospective business partner. Customer complaints will give a beneficial profitability and goodwill to the company to seek their weakness and improve their performance in order to give better services to the customers.